A framework for impact analysis of small hydropower on river ecological integrity - Li,X; Wang,Y; Buytaert,W; Ji,Q; Liang,R; Li,K (Water Research, 2025)
Under the pressure of small hydropower development, the ecological integrity of small- and medium-sized rivers in mountainous regions has deteriorated, hindering the normal functioning of mountain ecosystem processes and diminishing the value of ecosystem services. Government agencies and environmental organizations worldwide have enacted legislation and guidelines aimed at assessing the integrity of river ecosystems. However, the mechanisms for maintaining river ecological integrity across different disciplines remain unclear, and there is a lack of analytical frameworks for the quantitative assessment of small hydropower impacts on river ecosystems. This study used a typical mountain river affected by small hydropower development as a case study and conceptualized river ecological integrity in terms of hydrological, habitat, and biological dimensions. A total of 10 hydrological indicators, 7 habitat indicators, and 17 biological indicators were identified as core indicators for describing ecological integrity. Comprehensive indexes for hydrological, habitat, and biological integrity were established and applied to a systematic quantitative assessment of the river’s ecological integrity. For rivers impacted by small hydropower development in mountainous regions, extreme flow events and flow dynamics were identified as the key elements in describing hydrological integrity, while connectivity, hydrodynamics, and riparian conditions were essential for characterizing habitat integrity. Biological integrity was described from the aspects of algae, macroinvertebrates, and fish species. The results showed that ecological integrity was degraded after the development of small hydropower. Significant degradations in ecological integrity were found in the water-reduced sections, with the integrity indexes of hydrology, habitat and biology declining by 48 %, 73 % and 8 % respectively. The findings provide new insights for addressing the degradation of river ecological in